Urolastic—A New Bulking Agent for the Treatment of Women with Stress Urinary Incontinence: Outcome of 12 Months Follow Up - Janusz Zajda; Fawzy Farag (Advances in Urology)
Objective. To evaluate the efficacy and safety of the new injectable implant, Urolastic, in women with stress urinary incontinence (SUI) after 12-month followup. Materials and Methods. A prospective, cohort study included adult women with SUI. Patients were treated with Urolastic periurethral injections under local anaesthesia. The injection procedure was repeated after 6 weeks when indicated. Patients were evaluated for efficacy and safety parameters 6 weeks, 3 months, and 12 months after therapy. Results. Twenty women 56 (33–71) years old were included. Thirteen patients (65%) received one injection each (overall average of 2,1 mL); 7 patients (35%) received a second injection. Nineteen patients complete the 12-month followup. The mean Stamey incontinence grade significantly decreased from 1.9 at baseline to 0.4 at 12 months (visit IV) (P<0.001). None of the patients were dry at baseline; 68% of them were dry at 12 months. The mean number of incontinence episodes significantly decreased from 6/day at baseline to 1.6/day at visit IV (P<0.001). Reduction in pad weight went from 20.2 to 7.8 g at one year. The mean I-QoL score significantly increased from 51 at baseline to 76 at visit IV (P<0.001). Six patients (30%) developed minor complications related to the injection procedure. Conclusions. Urolastic is effective and long-standing urethral bulking agent with moderate adverse events.